2021
DOI: 10.1016/j.ajoc.2021.101083
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of cases with retinal pigment epithelium aperture

Abstract: Purpose To report the clinical findings of the patients with retinal pigment epithelium (RPE) aperture secondary to age-related macular degeneration (AMD). Methods A retrospective data analysis was conducted of patients at the University of Tokyo Hospital eye clinic, from the year September 1st, 2012 to 2019. Review of the medical records of patients with RPE aperture accompanied by AMD was performed. We investigated age, best-corrected visual acuity (BCVA), images of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…The absence of RPE detachments and the morphology of the surrounding RPE, evidence of folds, or areas of traction can differentiate this entity from RPE apertures and tears that usually occur in relatively large dome-shaped RPE detachments. 1,3,4 The lack of leakage on FA helps differentiate SMARPE from other entities that present CNV.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of RPE detachments and the morphology of the surrounding RPE, evidence of folds, or areas of traction can differentiate this entity from RPE apertures and tears that usually occur in relatively large dome-shaped RPE detachments. 1,3,4 The lack of leakage on FA helps differentiate SMARPE from other entities that present CNV.…”
Section: Discussionmentioning
confidence: 99%
“…Querques et al 2 studied 10 eyes, most with drusenoid pigment epithelial detachment (PED) that developed such RPE defects. Similarly, Giannakaki-Zimmermann et al 3 reported 7 eyes with apertures, of which 4 displayed drusenoid PED, whereas Yoshinaga et al 4 studied 5 cases of RPE defect all associated with drusenoid PED.…”
mentioning
confidence: 99%